2009
DOI: 10.46298/dmtcs.460
|View full text |Cite
|
Sign up to set email alerts
|

On the chromatic number of some flip graphs

Abstract: Graphs and Algorithms International audience This paper studies the chromatic number of the following four flip graphs (under suitable definitions of a flip): the flip graph of perfect matchings of a complete graph of even order, the flip graph of triangulations of a convex polygon (the associahedron), the flip graph of non-crossing Hamiltonian paths of a set of points in convex position, and the flip graph of triangles in a convex point set. We give tight bounds for the latter two cases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…This means each of the remaining 3m + 4 − y blue diagonals is flipped at least twice. Hence, t III ≥ y + 2(3m + 4 − y) = 6m + 8 − y Together with (3), this becomes (10) y > 1.99m…”
Section: Strong Convexity Fails With Two Flat Verticesmentioning
confidence: 80%
See 1 more Smart Citation
“…This means each of the remaining 3m + 4 − y blue diagonals is flipped at least twice. Hence, t III ≥ y + 2(3m + 4 − y) = 6m + 8 − y Together with (3), this becomes (10) y > 1.99m…”
Section: Strong Convexity Fails With Two Flat Verticesmentioning
confidence: 80%
“…In this case, F(Σ) is the graph of a convex polytope-the associahedronwhose dimension is the number of vertices of Σ minus three [17]. The genus of this graph [21], its chromatic number [10], and hamiltonicity [15] have been investigated. Its geometry is specially interesting because of its relation with the rotation distance of binary trees [32,31].…”
Section: Introductionmentioning
confidence: 99%
“…We use χ(G) to denote the chromatic number of a graph G. Fabila-Monroy, Flores-Penaloza, Huemer, Hurtado, Urrutia and Wood [9] observed that χ(M(K n,n )) = 2 and using this result, proved that…”
Section: Introductionmentioning
confidence: 99%
“…Over recent decades there has been an increasing interest in graphs on combinatorial objects in which the adjacency relation reflects a local change, for example, flip graphs (see [2,4,10,11,13]). In this paper we introduce Yoke graphs, a family of flip graphs that generalizes previously studied families of graphs: colored triangle free triangulations [1] (CTFT), arc permutations [3] and geometric caterpillars [8].…”
Section: Introductionmentioning
confidence: 99%